Accurate timing of gamma rays with high-rate Resistive Plate Chambers - Lopes, L. (2007)
The counting rate capability of RPCs is strongly conditioned by the availability of suitable resistive materials for the electrodes. For time-of-flight measurements in heavy-ion high-energy physics, the extension of the counting rate capabilities achievable with glass electrodes, around 2 kHz/cm2, to much higher values is of fundamental importance. To address this issue we developed single-gap tRPCs with electrodes made from metal and from a commercially available ceramic material free of charge-depletion effects. Tests performed with 511 keV photons yielded a time resolution around 90 ps [sigma]. Neither the time resolution nor the efficiency have been affected by background rates of up to 20 kHz/cm2 produced with photons from an X-ray generator. The present result establishes the practical feasibility of accurate timing measurements with RPCs at rates up to 20 kHz/cm2, while keeping a time resolution below 100 ps [sigma].